The Effective Width in Composite Steel Concrete Beams at Ultimate Loads (Journal of Engineering, 2014)
A composite section is made up of a concrete slab attached to a steel beam by means of shear connectors. Under positive and negative bending moment, part of the slab will act as a flange of the beam, resisting the longitudinal compression or tension force. When the spacing between girders becomes large, it is evident that the simple beam theory does not strictly apply because the longitudinal stress in the flange will vary with distance from the girder web, the flange being more highly stressed over the web than in the extremities. This phenomenon is termed "shear lag". In this paper, a nonlinear three-dimensional finite element analysis is employed to evaluate and determine the actual effective slab width of the composite steel-concrete beams by using theAnalysis System computer program (ANSYS 11.0). The of elements were used (SOLID65, LINK8, SHELL143, COMBIN39, TARGE170 andCONTA174) to model the concrete slab, the steel reinforcing bars, the steel girder, the shear connectors (including uplift and dowel action), and the interface between top flange of the steel girder and concrete slab, respectively. Comparisons with experimental tests have been performed to validate the finite element analysis results. In general, excellent agreement between the finite element solution and the experimental results has been obtained. The maximum difference in ultimate load is about (2.9%). Finally, parametric studies have been carried out to investigate the effect of some important parameters; these parameters include the degree of interaction, slab thickness, slab width, concrete compressive strength ( ), distribution of shear connectors, reinforcement of slab, type of loading, and boundary conditions. The effect of changing these parameters causes variety in the effective slab width and the maximum stress reaches 40.7% and 28.5%, respectively.